Next-Generation Sequencing to Detect Pathogens in Pediatric Febrile Neutropenia: A Single-Center Retrospective Study of 112 Cases. (4th May 2021) - Horiba, Kazuhiro; Torii, Yuka; Okumura, Toshihiko; Takeuchi, Suguru; Suzuki, Takako; Kawada, Jun-ichi; Muramatsu, Hideki; Takahashi, Yoshiyuki; Ogi, Tomoo; Ito, Yoshinori
Abstract: Background: Febrile neutropenia (FN) is a frequent complication in immunocompromised patients. However, causative microorganisms are detected in only 10% of patients. This study aimed to detect the microorganisms that cause FN using next-generation sequencing (NGS) to identify the genome derived from pathogenic microorganisms in the bloodstream. Here, we implemented a metagenomic approach to comprehensively analyze microorganisms present in clinical samples from patients with FN. Methods: FN is defined as a neutrophil count <500 cells/µL and fever ≥37.5°C. Plasma/serum samples of 112 pediatric patients with FN and 10 patients with neutropenia without fever (NE) were sequenced by NGS and analyzed by a metagenomic pipeline, PATHDET. Results: The putative pathogens were detected by NGS in 5 of 10 FN patients with positive blood culture results, 15 of 87 FN patients (17%) with negative blood culture results, and 3 of 8 NE patients. Several bacteria that were common in the oral, skin, and gut flora were commonly detected in blood samples, suggesting translocation of the human microbiota to the bloodstream in the setting of neutropenia. The cluster analysis of the microbiota in blood samples using NGS demonstrated that the representative bacteria of each cluster were mostly consistent with the pathogens in each patient. Conclusions: NGS technique has great potential for detecting causative pathogens in patients with FN. Cluster analysis, which extracts characteristic microorganisms from a complex microbial population, may be effective to detect pathogens in minute quantities of microbiota, such as those from the bloodstream. Abstract : Metagenomic next-generation sequencing was used to diagnose pathogens in 17% of pediatric patients with febrile neutropenia with negative blood culture test results. Metagenomic blood analysis suggested translocation of the human microbiota into the bloodstream in neutropenia.